Antioxidant and cytotoxic properties of smilax zeylanica L.(Family :Smilacea) root rhizomes - Malge, N.; Peiris, D.C (My University, 2017)
attached

Cancer patient often attracted to complimentary alternative medicinal practices due to their natural origin, lack of side effects. Roots and rhizomes of Similax zeylanica is an important herb in traditional medicine against arthritis, diabetic and cancer. Hence, this study aims to evaluate the antioxidant and cytotoxicty activities of root extracts. Air dried roots and rhizome (RR) were refluxed with water and methanol to obtain aqueous (ARRE) and methanol (MRRE) extracts. Both extracts were screened for phytochemicals and confirmed by thin layer chromatography. Total phenols, flavonoids were quantified using Gallic acid and quarcetine as the respective standards. Free radical scavenging activity (doses: 2-300μ/ml) was evaluated by 2,2 diphenyl-1- picrylhudrazyl DPHH assay (n 3), while cytotoxicty (doses: 8, 80, 90, 100, 666 μg/ml) was tested (n=50) using brine shrimp lethality assay. Saponnins, flavonoids, pronthocynidine, tannins and polyphenols were detected in both extracts. Furthermore, MRRE contained unsaturated sterols, tri tepenes, and anthraquinones. Both MRRE and ARRE showed a linear relationship with the total phenol and flavonoid contents with their respect standards. For both extracts increasing free radical scavenging activity was observed with increasing concentration A significant linear relationship was observed in the cytotoxic assay compared to the positive control . The present study revealed that the methoanol extracts of the RR of S.zeylanica contains potent cytotoxic properties and verifies its ethno-medicinal values.
Keywords: smilax zeylanica; roots rhizomes; Antioxidant; cytotoxicity